Оптимізація режиму руху порожнього електричного транспортного засобу на прямолінійному горизонтальному відрізку колії - Мокін, Олександр Борисович; Мокін, Борис Іванович (НТУ "ХПІ", 2010)
There had been presented the results of solving an optimization problem of the empty electric vehicle on straight horizontal part of the path by minimum consumption criteria. There had been created the mathematical model for optimal speed of empty electric vehicle and the optimum anchor chains current of traction electric drive.
Optimization of empty electric vehicle on straight horizontal part of path
Keywords: тяга електрична; транспорт залізничний; електропривід; функція Лагранжа; модель математична